LA BIOÉTICA DE LAS VIRTUDES Y SU INTERFAZ CON LA AGENDA 2030 DE LAS NACIONES UNIDAS: POSIBLES REFLEXIONES Y SUS REPERCUSIONES SOBRE LA PROMOCIÓN DE LA SALUD EN LA EDUCACIÓN SUPERIOR (Revista Inclusiones, 2020)
Background: This study sought to identify the connections between the principles related to virtue bioethics (VB), the objectives of the United Nations 2030 Agenda for Sustainable Development (UN) and the references on health promotion (HP), mainly targeted at professors. Agenda 2030's Sustainable Development Goal (SDG) 3 - “Ensuring healthy lives and promoting well-being for all at all ages” - reflects on the connections between the VB paradigm and HP. VB and HP value interactions between individuals and, in this approach, establish relationships with the 2030 Agenda, providing a way to stimulate and develop useful and viable measures that involve health and wellbeing, quality of life, happiness, solidarity and empathy. Both approaches are built on this same perspective, as they interpret the human person as a being in continuous development and are respected in their integrity and their lived experiences. Objective: To present and identify the interfaces between VB and the UN Agenda 2030 as a substrate for the development of bioethical interventions involving HP in higher education. Methodology: exploratory-descriptive and quantitativequalitative approach. Sample: professors from southern Brazil, random sampling, non-probabilistic for convenience, CI = 95%, n = 1400 professors. Approved by the Research Ethics Committees of the HCPA, Brazil, University Fernando Pessoa, Portugal and CAAE 55066616.8.0000.5327, Plataforma Brasil. Results: extraction of 6 main components through factor analysis, categorised and interpreted by qualitative content analysis, according to Bardin. Conclusions: The results suggest that moral principles such as respect for dignity, health care, protection, sustainable actions, prosperity, peace, solidarity and empathy were reported by the surveyed professors, with a positive impact on their health. The promotion of individual and collective well-being, quality of life, inclusion and social justice are paradigms associated with VB and HP, and whose principles are correlated with the 2030 Agenda in their SDGs.